STRATEGIC APPROACHES TO PROMOTING EXCLUSIVE BREASTFEEDING AMONG MOTHERS OF PREMATURE BABIES: A QUALITATIVE STUDY - Hidayah, Seventina Nurul; Zukrufiana, Ilma Ratih; Rizqi, Intan Christy Mayasari (Journal of Advanced Nursing and Health Sciences, 2025)
Background: The provision of exclusive breastfeeding for premature infants often faces challenges due to the infant's inability to breastfeed directly from the breast, which hinders the initiation of breastfeeding and the success of exclusive breastfeeding. According to data from the Slawi Public Health Center, the coverage of exclusive breastfeeding for premature infants remains low. This study aims to analyze strategies for implementing exclusive breastfeeding and to identify its supporting and inhibiting factors.Methods: The research method employed a qualitative approach with accompaniment provided to two mothers with infants aged â‰¤4 months who were committed to exclusive breastfeeding, along with two triangulation informants. The accompaniment was carried out until the infants reached six months of age through home visits conducted two to three times.Results: The findings revealed a strong commitment from mothers to maintain exclusive breastfeeding, despite external pressures such as the promotion of formula feeding and early complementary feeding. Intensive mentoring, family support, and health education were identified as the main supporting factors. Meanwhile, the lack of understanding among the surrounding community emerged as a significant barrier, which should be addressed through continuous educational interventions.Conclusion: In general, exclusive breastfeeding practices for premature infants in the Slawi area are considered satisfactory. It is recommended that the local health center continue providing ongoing support to mothers to maintain exclusive breastfeeding for the first six months and continue breastfeeding up to two years, particularly for mothers of premature infants.